Sources and transformation of nitrate aerosol in winter 2017–2018 of megacity Beijing: Insights from an alternative approach. (15th November 2020) - Zhang, Zhongyi; Guan, Hui; Luo, Li; Zheng, Nengjian; Xiao, Hongwei; Liang, Yue; Xiao, Huayun
Abstract: The dual isotopic signatures of particulate nitrate (hereafter as δ 15 N–NO3 - and δ 18 O–NO3 - ) have been extensively used to imprint the source and chemical transformation of atmospheric NO x (NO x  = NO + NO2 ). For instance, the δ 18 O–NO3 - elevated proportionally when NO x converted by O3 . In the present study, daily PM2.5 samples (n = 91) were collected in winter Beijing (December to February in 2017–2018) and a two-endmember linear isotopic mixing model was used to model the endmember δ 18 O values of NO3 − oxidized by O3 (termed as δ 18 Onoct ) and the contribution of the different pathways (i.e., daytime and nocturnal oxidation pathways). During the campaign, the NO3 − concentrations in PM2.5 varied from 0.3 to 46.3 μg m −3 (8.1 ± 9.8 μg m −3 ), δ 15 N–NO3 - from +1.0‰ to +19.6‰ (12.5 ± 3.6‰) and δ 18 O–NO3 - from +50.7‰ to +103.5‰ (74.9 ± 13.3‰). The Keeling plots indicated that the δ 18 Onoct endmember value was within the ranges based on theoretical approaches. The contribution of the nocturnal pathway to NO3 − in PM2.5 ranged from 8.5 ± 3.2% in background days to approximately 100% in extremely polluted days, with a mean of 52.0 ± 25.5%. The determined δ 15 N–NO3 - values (12.5 ± 3.6‰) were comparable with previous studies conducted in recent winter Beijing (2013–2017, i.e., average values of 11.9‰–13.8‰). Due to the optimization of energy structure in Beijing, we inferred that the dominant NO x source in recent wintertime was the vehicular exhaust. The Bayesian mixing model also confirmed that the contribution of vehicle exhaust/biomass burning sources to the NO3 − was up to 70%. This study may further improve the understanding of NO x emission source and atmospheric processes in urban environments. Highlights: Two-endmember linear isotopic mixing model can simulate the δ 18 O values of NO3 − oxidized by O3 . OH channel accounted for 48% of the wintertime NO3 − production in Beijing. Vehicular exhaust was the major NO x source in winter 2017–2018 of Beijing.